A degeminação no italiano em frase fonológica reestruturada - Hogetop, Denise Nauderer (2010)
This study is about one of the shandi fenomena, named degemination, in Italian. Degemination is the fusion of the first vowel, in a sequency of two vowels of same quality VV, in which the first vowel is at the end of a word and the second one occupies the begining of the following word. This study aims to prove that the blocking of degemination in Italian is the stress of the phonological sentence, when it is placed on the second vowel of the sequence, like it is in Brasilian Portuguese. Based on the framework of the Prosodic Theory (Nespor and Vogel, 1986), on the Ritmic Phonology (Nespor, 1993) and on the external shandi studies for the Brasilian Portuguese (Bisol, 1996a, 1996b, 2003) we have verified that the real block to the rule aplication in Italian is the stress of the phonological sentence.